(3OQQ GdfMhQ aj eOGFM Gdedc GdefUhQs - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj CWdY fLhe GdeYGfj GdeVjFI aj BaGb NhGWQ GdaUMGA hEf CWjH GdKfGA GdePNhQ QGLY eaQhVg Edi efGbH GdefUhQ s
(3BNQgG (B:s
(3aEf Cgdc abO CHbjJ HYOj ShGQA JYLH GdeJeKdjfG dPjPGJ GdebGWY QGFbGJ dh Cf GdTYQ jdHS dGQJOjfG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B316 - (3U(B354s
(3GfXQ GdLRA GdChd Qbe (B228 (3COHs
(3hQO CjVkG JMJ Qbe (B476s
(3ojYQa CjVkG HGdbUGFO GdCQJbjGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs